(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2022)
Many Radio frequency circuits such as low noise amplifiers, voltage-controlled oscillators, and RF filters need inductors for realization. Passive and spiral implementations of the inductors have many limitations precisely when these RF circuits are designed and realized as integrated circuits. Typically, standard structure realized active inductors provide a limited inductor value and quality factor. This paper presents an alternative active Complementary Metal-Oxide Semiconductor realization based on the use of a gyrator-c configuration that is suitable for integrated circuit fabrication. A comparative study between various active inductor realization topologies is performed to obtain and improve active inductor performance. The most important parameters that have to be investigated are the quality factor, the range of inductors value at the specified operating frequency, and the self-resonant frequency. It is shown that the use of passive feedback improves active inductor performance, however large passive resistance is required that is not suitable for IC fabrication. An alternative MOS transistor and voltage divider structures are used to replace the passive feedback resistor that improves performance without requiring a large chip area for fabrication. It is also shown that different transistor dimensions and current source values result in different performance parameters. Therefore, minimized transistors dimensions are required for minimum chip area, and also minimized current values are required to minimize power consumption. It is shown that the voltage divider AI realization resulted in a significant improvement in inductance value (L=20.16 nH) and higher quality factor (Q=3.078) compared to other topologies.